Digital Banking Transformation and Financial Inclusion: A Comparative Regulatory Review - Alya Nabila Adistia; Ayu Ambarwati; Fidya Pramesti (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
Digital banking transformation has emerged as a central driver of financial inclusion, yet its distributive outcomes vary substantially across regulatory environments. This study conducts a structured comparative regulatory review to examine how variations in legal design, supervisory capacity, and governance coherence mediate the relationship between digital banking transformation and financial inclusion. Drawing on a systematic literature review of peer-reviewed scholarship and regulatory documents, the analysis integrates comparative institutional theory with regulatory governance frameworks. Findings reveal that proportional and adaptive regulatory architectures facilitate balanced innovation and prudential oversight, thereby enhancing both access and quality dimensions of inclusion. Higher transformation intensity—characterized by interoperable platforms, mobile ecosystems, and digital-only banking models—correlates with diversified service usage and broader socio-economic impacts, including growth and sustainability alignment. However, digital divides, infrastructural disparities, and governance fragmentation moderate inclusive outcomes. The study advances a conceptual framework positioning regulatory complementarity as the critical mediator linking technological innovation to inclusive development, offering theoretical refinement and policy-relevant insights for sustainable digital financial ecosystems.